A’joot : Ethics, Rights and Values Spoken from the Stomach and Heart - Araceli Rojas (International Journal of Critical Diversity Studies)
This article examines the meaning of human rights. First, it describes the notions that are generally understood only from a Euro-Western view and position, which has created a universalising list of rights, reproducing paternalising and vertical power relations. Second, this text discusses double standards practices from the West that have unfairly divided the world into people with rights and those without merit. Third, this article attempts to raise new ways to conceive and address human values that are inspired by the philosophies and ways of relating to the world among Indigenous peoples. Some examples will be given which come from the Ayöök people of Oaxaca, such as the a’joot expression which asks for speaking from the stomach and heart, and where the human cannot exist as an individual-self without the presence of others in society. Emphasis is given to the concept of dignity developed by the Zapatistas (Zapatista Army of National Liberation), which entails the recognition of present living without dignity while fighting to achieve it, as a scream-protest against invisibilisation and an ongoing development of its meaning.